New species of Neanuridae (Collembola) from Wuyunjie National Nature Reserve, China - Jiang, Ji-Gang; Wang, Yi; Zhu, Pei-Ting (Zootaxa, 2025)
Two new species of Neanuridae are recorded and described from Wuyunjie National Nature Reserve, Taoyuan County, Changde City, Hunan Province, China. Paralobella sensilla sp. nov. is characterized by body tubercles well differentiated; 3+3 eyes; cephalic chaeta O present; cephalic tubercles Dl separate from tubercle L+ So; mandible with 2 basal teeth and four apical teeth; maxilla with only one tooth; tubercle De fused to Dl on Abd. V; and dorsal body chaetae s clavate. Vitronura clavata sp. nov. is characterized by 2+2 eyes; cephalic chaeta O present; body tubercles well differentiated; cephalic tubercles Dl, L and So fused; mandible with one basal, one middle and four apical teeth; maxilla with two lamellae, each with one tooth; dorsal body macrochaetae usually clavate; and unguis with an inner tooth. All species of both genera are also listed and their distribution is provided.